Driving Factor of Indonesian Muslims' Intention in Household Food Waste Management: Generational Comparison - Anggiana Diniary; Kenny Devita Indraswari; Tika Arundina (AL-MUZARA'AH, 2024)
Food waste in Indonesia is predicted to increase if the problems are not taken seriously. The role of food waste management is essential to reduce its effects on the environment, society, and economy. Studies on the driven factor of intention to manage household food waste between generations are still limited. We address this gap by developing a research model with the Theory of Interpersonal Behavior includes economic and religiosity factors to explain food waste management behavioral intention between generations. The result shows that anticipated guilt, sense of community, awareness of consequences, environmental knowledge, financial concern, and religiosity are positively associated with managing food waste in generations Y and Z. However, this study did not find a significant relationship between financial concern and recycling intention. Further, anticipated guilt did not have an impact on the reuse intention of Generation Y, financial concern factor did not significant on the reuse intention of Generation Z, and religiosity did not show an impactful effect on reducing, reusing, and recycling intentions of Generation Z. The findings provide implications for developing strategies to encourage food waste management in Indonesia household.